2015
DOI: 10.1016/j.rfe.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

How much can lack of marketability affect private equity fund values?

Abstract: This paper derives an upper bound on the discounts for lack of marketability of private equity funds using option‐pricing theory. The upper bound is a function of the volatility of the fund returns, of the (remaining) lifetime of the fund, of two parameters governing the speed of capital drawdowns and distributions, of the volatility of the stock market returns, and of the return correlation between the fund and the stock market. The model calibration and numerical analysis deliver several novel insights about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Borrowing future profits has its limitations, and reporting higher profits before IPOs causes their excessive decline in the next period. Buchner (2016), in his work, examined the size of the discount for the lack of liquidity of private equity funds. His research showed that the upper limit of the discount for lack of liquidity is 7%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Borrowing future profits has its limitations, and reporting higher profits before IPOs causes their excessive decline in the next period. Buchner (2016), in his work, examined the size of the discount for the lack of liquidity of private equity funds. His research showed that the upper limit of the discount for lack of liquidity is 7%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers and practitioners have also focused on the valuation of minority discount for lack of marketability in the sale/purchase transactions of minority interests which cannot be easily sold to third parties within a reasonable period of time and for a fair value due to their absolute irrelevance from qualitative and quantity stand-point (Buchner, 2016;Chipalkatti & Luft, 2013;Finnerty, 2013;Lazar & Prisman, 2012). Notwithstanding such issue falls outside the scope of this article and it is a discount applied to minority interests in companies listed on official markets, similarly to the previous circumstance, also this one has some common points therefore it may be taken partially as reference in this analysis.…”
Section: Literature Overviewmentioning
confidence: 99%